Return to sport following amputation - Matthews, D.; Sukeik, M.; Haddad, F. (The Journal of Sports Medicine and Physical Fitness, 2014)
Amputation in athletes has a substantial impact on lifestyle and sporting activity, as well as self-perception and quality of life. The impact of limb loss on athletic ability will vary depending on the cause of amputation and the anatomical location of the amputation. The use of sporting activity for rehabilitation of amputees was first introduced in 1944 at Stoke Mandeville Hospital. The first international paralympic games were founded in 1960. Following these events the opportunity to participate in sport following limb loss has increased significantly. Sport participation has been aided by the development of sporting prostheses, however multiple factors will determine the exact prosthesis used. These include the nature of the sporting activity as well as the level of the amputation. The biomechanics involved in walking and running are altered following the loss of a limb or part thereof. This can cause subsequent degenerative changes within the remaining joints on the amputated limb as well as the contralateral limb. Factors affecting return to sporting activity are multivariate and inter-related, including patient factors, surgical factors, nature and level of the sporting activity and prosthetic factors. The authors review current literature, detail predictive factors of return to sport and the physical and psychosocial impact on patients following limb amputation.